MicroRNA co-expression patterns unravel the relevance of extra cellular matrix and immunity in breast cancer. (June 2018) - Dugo, Matteo; Huang, Xiaoyan; Iorio, Marilena V.; Cataldo, Alessandra; Tagliabue, Elda; Daidone, Maria Grazia; Wu, Jiong; Orlandi, Rosaria
Abstract: Background: Aberrant microRNA (miRNA) expression is associated with human tumors, including breast cancer (BC), and has diagnostic and therapeutic potential. BC tissue is characterized by distinctive miRNA signatures associated with cancer development or progression. Methods: We explored miRNA profiles from BC tissues by unsupervised hierarchical clustering. Functional analysis was based on miRNA-mRNA data integration and Gene Set Enrichment Analysis. Results: Partition of miRNA expression data from BC samples of Chinese Han and Caucasian subjects identified clusters of correlated miRNAs that were subjected to a global and integrative analysis aimed at identifying novel associations with biological and clinical value. Co-expression of miRNAs clustered in the same module was partially explained by co-transcription of the same genomic locus or involvement in similar biological functions. No significant associations were found among miRNA clusters and clinical-pathological variables, except for ER status and immune infiltration estimated by CIBERSORT. A large number of miRNA clusters, instead, were significantly differentially expressed in PAM 50 and extracellular matrix (ECM) subgroups. Specifically, a new cluster including several relatively new miRNAs was overexpressed in ECM3 tumors, characterized by increased epithelial to mesenchymal transition (EMT). An integrative approach to extract meaningful relationships on miRNA/mRNA networks and predict the functional role of the miRNA clusters indicates that immune system, ECM, proliferation, transcription and DNA repair were the biological functions more targeted by miRNAs aberrantly expressed in BC. Conclusions: We then identified novel miRNA patterns associated with BC molecular features, and described a complex regulatory network where miRNAs belonging to the same module cooperate in finely tuning gene expression. Highlights: We identified co-expressed miRNA modules in breast cancer. miRNA aberrant expression is mainly associated to differentiative and hormonal features. miRNA modules cooperate in finely tuning cellular and microenvironmental processes.